Consumo colaborativo como alternativa ao consumismo: análise de experiências em espaços de coworking e guarda-roupas compartilhados - Lima, Fernanda Imada de (2023)
In today's society, consumption is a process of inclusion and social ascension within a capitalist culture aimed at capital accumulation. Capitalism accentuates social ills such as inequality, violence, and intolerance, just as it instigates selfishness, competitiveness, and individual behavior, weakening collective processes based on solidarity and companionship. However, the search for options contrary to the current economic model progressed as the discussion on sustainability helped infuse the primordial search for environmental conservation as a value to consider in ethical and consumption decisions. Thus, some people reflexively begin to question why they have an unused object at home, leaning against the shelf when it could be helpful to someone. Collaborative consumption (CC) arises as one of the innovations that promise to be fairer from an economic, social, and environmental perspective. CC is a social practice and an economic model promoted by individuals and organizations with principles rooted in collaboration between suppliers and consumers. Information and communication technologies enable the transactions and interactions between the stakeholders. One of the premises of this model is to facilitate access to the detriment of possession, providing a new way of experiencing consumption and the relationship with goods. Due to the relevance of the topic and given the urgency of discussing viable solutions for the various socioeconomic and environmental crises that the contemporary world faces, this study aimed to analyze the phenomenon of collaborative consumption in the national territory from the experiences of customers and entrepreneurs of coworking spaces and shared wardrobes. Initially, the researcher identified the need to contextualize consumption dynamics and consumer behavior over modern human history. Subsequently, the collaborative consumption experiences analysis took place to understand the participants' motivation, investigate whether social ties emerged, and identify the strengths and weaknesses in developing these initiatives. Data collection happened through online semi- structured interviews. The method selected for the data analysis was Bardin's content analysis. The results revealed that consumers use collaborative consumption platforms mainly for practical reasons, such as saving money and convenience. On the other hand, entrepreneurs are motivated both by the desire or need to endeavor and the search for a job with a purpose beyond obtaining income. A significant barrier to collaborative consumption in respondents' perception is the need for more knowledge. Most customers said they did not feel part of a group with common interests. Entrepreneurs claimed to be unable to make significant profits from their ventures. These results will help understand the mechanisms behind the consumption process better, guide regulations to protect the parties involved in the CC, and encourage the creation of incentives for developing collaborative businesses. Keywords: sustainability; consumerism; collaborative consumption; coworking; shared closet